Ectopic endoreduplication caused by sterol alteration results in serrated petals in Arabidopsis - Hase, Yoshihiro (Journal of experimental botany, 2005)
The Arabidopsis frill1 (frl1) mutant, that has serrated petals and sepals but no other large changes in plant morphology, was studied. The frl1 had a mutation in STEROL METHYLTRANSFERASE 2 and an altered sterol composition. It was found that the frl1 mutation causes ectopic endoreduplication in petal tips that do not normally endoreduplicate. The rosette leaves of frl1 also showed an enhanced level of endoreduplication, but their morphology was hardly affected. These facts suggest that the suppression of endoreduplication is important for petal morphogenesis and the normal sterol composition is required for this suppression